Relationship between dietary vitamin D and serum 25-hydroxyvitamin D levels in Portuguese adolescents - Cabral, M (2018)
Objective: To understand the relationship between vitamin D intake and serum 25-hydroxyvitamin D (25(OH)D) levels in a sample of Portuguese adolescents. Design: Cross-sectional evaluation carried out in the 2003/2004 school year. Vitamin D intake was assessed by an FFQ and 25(OH)D was measured in a fasting blood sample. Setting: Public and private schools in Porto, Portugal. Subjects: Adolescents aged 13 years (n 521) enrolled at school (EPITeen cohort). Results: Both mean (sd) intake and serum 25(OH)D level were far below the recommended, 4·47 (2·49) µg/d and 16·5 (5·7) ng/ml, respectively. A significant difference in serum level was found according to season, with lower values in winter than summer (14·8 (4·6) v. 17·3 (5·9) ng/ml, P<0·001). Vitamin D intake was weakly correlated with serum 25(OH)D (r=0·056, P=0·203). Conclusions: Dietary vitamin D and serum 25(OH)D levels were positively but weakly correlated and the error was higher among those with higher serum 25(OH)D concentration. Our results support the need for strategies that promote increase of the most important food sources of vitamin D to reduce the high prevalence of low vitamin D status.